The Papers of Thomas Jefferson, Volume 13 : March 1788 to October 1788 - Jefferson, Thomas, 1743-1826 (Book collections on Project MUSE., 1950)
"The Papers of Thomas Jefferson is a projected 60-volume series containing not only the 18,000 letters written by Jefferson but also, in full or in summary, the more than 25,000 letters written to him. Including documents of historical significance as well as private notes not closely examined until their publication in the Papers, this series is an unmatched source of scholarship on the nation's third president."--Publisher description.